Analysis of Soil and Water Samples Collected From Sugar Estate, Sunti, Niger State - Aliyu Ahmed, Ibrahim; Abdullahi, Muhammad; Hauwa Larai, Muhammad-Idris; Aisha, Dyadya (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Environmental pollution is a critical global health issue, particularly in low- and middle-income countries. This is caused chiefly by anthropogenic activities such as mining, refining, smelting, and agricultural operations, which have led to an increasing rate of environmental pollution by metals. Agricultural factories pollute the environment due to the constant release of factory waste without proper treatment before discharge. This is alarming and deserves proper attention. This is alarming and deserves proper attention. Since soil is an important aspect of our environment it serves as a sink for natural and anthropogenic processes, thereby resulting in bioaccumulation of toxic substances in plants and transferred along the food chain. Analysis of soil and wastewater from selected locations around a sugar factory was carried out using a microwave plasma atomic emission spectrometer. Eight samples consisting of water and soil were collected from three sites. The trend for results with instrument number MY19479002 is iron> cadmium > chromium > zinc >lead. The values obtained for cadmium (1.68-2.08 mg/L) are above the permissible limit while other metal concentrations were below the permissible limit of water. Also, the concentration of heavy metals in soil samples was within the range of 0.24 - 0.29, 0.03 - 0.56, 0.12 - 1.10, 0.09-below detection and 0.74 - 13.85 mg/kg for zinc, chromium, cadmium, lead and iron respectively. The observed concentration in soil samples was within the permissible limits in agricultural soils. Thus, suitable for agricultural activities.